Sumbangan dan Peranan KH. Abdul Hamid dalam Kearifan Tempatan: Kajian Terhadap Kitab Tarjuman: Contribution and Role of KH Abdul Hamid in Local Wisdom: A Study on the Book of Tarjuman - Imamuddin; Ali, Abdul Karim (Al-Basirah Journal, 2022)
This study will discuss the thought of KH. Abdul Hamid in the Kitab of Tarjuman (1800-1900 BC) on the subject of law. The Kitab of Tarjamun was extensively read by the students, scholars, sheikh, and the society at large, particularly in the Pamekasan regency, East Java. The Kitab of Tarjamun is essentially the kitab of tawhid (oneness of God) and fiqh (Islamic jurisprudence). However, its extensively discuss the subject of fiqh muammalah, to name a few, such as taharah (abolition), prayer, fasting, inheritance, pilgrimage, marriage, and the general discourse. The objective of this study is to identify the roles of the KH Abdul Hamid’s thought in the Kitab of Tarjamun. To meet this objective, the researcher uses a qualitative method of library research. The study finds that the thought of KH Abdul Hamid has crucial roles in following areas, such as karapan sapi (the festival of cow racing). Hence, the Kitab of Tarjuman introduced by KH Abdul Hamid can solves the social issues and problems in Pamekasan.